Mathematical literacy learning environment for inclusive education teachers: A framework - Risdiyanti, Irma; Zulkardi; Putri, Ratu Ilma Indra; Prahmana, Rully Charitas Indra (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
The Program for International Student Assessment (PISA) 2022 study revealed low mathematical literacy scores among students, including those in inclusive education settings. A significant factor contributing to this issue is the inadequate capacity of teachers to effectively teach mathematical literacy. In response, this study aimed to design a mathematical literacy learning environment framework to enhance teachers' theoretical and practical understanding of teaching mathematical literacy in schools. The research employed a design research methodology, specifically the development study type, which involved preliminary research, prototype development, and evaluation stages. This paper focuses on the preliminary research phase, where data were collected through literature reviews and focus group discussions (FGDs) with teachers from inclusive schools. The collected data were analyzed qualitatively and descriptively. The study successfully developed a framework for a mathematical literacy learning environment that integrates courses, social media, and community engagement. This framework is intended to serve as a comprehensive reference for improving teachers' capacity to teach and assess students' mathematical literacy in a more holistic manner.